BRICS COOPERATION AS A NEW FORMAT OF THE INTEGRATION PROCESS - A. N. Vergun (Vestnik MGIMO-Universiteta)
The article deals with the analysis of the phenomenon of the BRICS countries, the reasons for their rise and consolidation at the beginning of the XXI century. The author notes that cooperation of BRICS is a new format for the integration of the leaders of the emerging countries, analyzes the political and economic cooperation of these countries within the group, as well as with the rest of the world and the specific nature of relations between BRICS in different periods of modern history. The author also calls attention to the response of the Western countries to the creation of this integration group. In conclusion, the author means that the world is entering a new era. It becomes more democratic and more open for interaction processes. The new global players have already appeared at the world scene, they get ready to change the old rules of the game and create new opportunities for themselves and for others.